2017
DOI: 10.17221/41/2016-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salsolinol on ACTH and cortisol response to handling stress in early anestrous sheep

Abstract: Hasiec M., Szlis M., Chmielewska N., Górski K., Romanowicz K., Misztal T. (2017): Effect of salsolinol on ACTH and cortisol response to handling stress in early anestrous sheep. Czech J. Anim. Sci., 62, 130-139.Inhibition of hypothalamic-pituitary-adrenal (HPA) axis activity by salsolinol was demonstrated in lactating sheep. We assessed whether salsolinol regulates, besides lactation, also adrenocorticotropic hormone (ACTH) and cortisol release, and if its action is prolactin-dependent. We examined two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, these studies did not examine changes over a 24-hour period. Studies performed in our laboratory also suggested the lack of differences in basal plasma ACTH and cortisol concentrations between midlactating and anestrous or postweaning sheep [ 28 , 29 ]. Furthermore, a study on Japanese macaques ( Macaca fuscata ) showed that lactating females had even lower fecal glucocorticoid concentrations than cycling females during the mating season [ 30 ].…”
Section: Hpa Axis Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…However, these studies did not examine changes over a 24-hour period. Studies performed in our laboratory also suggested the lack of differences in basal plasma ACTH and cortisol concentrations between midlactating and anestrous or postweaning sheep [ 28 , 29 ]. Furthermore, a study on Japanese macaques ( Macaca fuscata ) showed that lactating females had even lower fecal glucocorticoid concentrations than cycling females during the mating season [ 30 ].…”
Section: Hpa Axis Activitymentioning
confidence: 91%
“…In order to verify this observation, we conducted serial salsolinol intracerebroventricular injections in anestrous sheep subjected to handling stress at the turn of winter and spring, when prolactin secretion was significantly reduced [ 13 ]. As a result of salsolinol injections, sheep had lower ACTH and cortisol response to stress compared to vehicle-treated animals, but there were no changes in plasma prolactin concentration, confirming that salsolinol action in regard to the HPA axis occurred without prolactin mediation [ 29 ]. Oxytocin should also be considered as a potential mediator of the discussed phenomenon, since salsolinol can mediate suckling-induced release of this hormone in lactating sheep [ 113 ]; however, it still remains to be investigated.…”
Section: Salsolinol: a New Putative Inhibitor Of Hpa Axis Activitymentioning
confidence: 97%
“…For analyses of blood parameter data during the transport phase, injection treatment (CRFA and SAL), collection time [pre-transport ( Pre-T ) and post-transport ( Post-T )], and their interactions were used as fixed effects. The time it took in seconds to take blood (measured from the moment the pig was handled to the end of blood collection) was used as a covariate when significant ( p ≤ 0.05) for plasma cortisol and ACTH levels because animal handling time directly influences ACTH and cortisol release ( Hasiec et al, 2017 ; Rocha et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is also one of the leading sheep breeds used for meat on a global scale (Rasali et al 2006;Maximini et al 2012). Sheep known as animals with year-seasonal oestrus activity depending on daylight conditions (Hasiec et al 2017;Molik et al 2017) are limited in their productive traits for https://doi.org/10.17221/21/2018-CJAS non-prolific period. Therefore, the effort is aimed at improving lamb growth abilities; especially in breeds intended for paternal position in breeding scheme for meat production.…”
mentioning
confidence: 99%